Wastewater-based epidemiology for tracking bacterial diversity and antibiotic resistance in COVID-19 isolation hospitals in Qatar - A.A., Johar (2023)
BackgroundHospitals are hotspots for antimicrobial resistance genes (ARGs), and play a significant role in their emergence and spread. Large numbers of ARGs will be ejected from hospitals via wastewater systems. Wastewater-based epidemiology has been consolidated as a tool to provide real-time information, and represents a promising approach to understanding the prevalence of bacteria and ARGs at community level. AimsTo determine bacterial diversity and identify ARG profiles in hospital wastewater pathogens obtained from coronavirus disease 2019 (COVID-19) isolation hospitals compared with non-COVID-19 facilities during the pandemic. MethodsWastewater samples were obtained from four hospitals: three assigned to patients with COVID-19 patients and one assigned to non-COVID-19 patients. A microbial DNA quantitative polymerase chain reaction was used to determine bacterial diversity and ARGs. FindingsThe assay recorded 27 different bacterial species in the samples, belonging to the following phyla: Firmicutes (44.4%), Proteobacteria (33.3%), Actinobacteria (11%), Bacteroidetes (7.4%) and Verrucomicrobiota (3.7%). In addition, 61 ARGs were detected in total. The highest number of ARGs was observed for the Hazem Mebaireek General Hospital (HMGH) COVID-19 patient site (88.5%), and the lowest number of ARGs was found for the HMGH non-patient site (24.1%). ConclusionThe emergence of contaminants in sewage water, such as ARGs and high pathogen levels, poses a potential risk to public health and the aquatic ecosystem.